An approximation to the study of the relationship between starch concentration in the tree and its effect on fruit retention in avocado cv. Hass in the Andean tropics of Caldas, Colombia - Arias-García, Juan Sebastián; Hurtado-Salazar, Alejandro; Ceballos-Aguirre, Nelson (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Low fruit set percentage, massive fruit drop, and low final retention continue to challenge researchers worldwide due to their direct impact on crop productivity. Among the factors influencing fruit retention, starch concentrations in the flowers have been noted to play a significant role; specifically, higher starch concentrations in the ovaries are associated with greater retention rates. The aim of this study was to determine the effect of starch concentrations in the trunk, roots, flower ovary and young shoots on both the initial and final retention of 'Hass' avocado fruit in two contrasting zones of the Andean tropics of Caldas, Colombia. The research was conducted in two commercial orchards situated at different altitudinal ranges in the Caldas department. Evaluations focused on 5-year-old 'Hass' avocado trees. Starch concentrations were measured in the roots, trunk, young shoots, and flower ovaries. Throughout the study, the number of flowers and fruit retention rates were monitored until harvest. Additionally, light and photosynthetically active radiation (PAR) levels were recorded and correlated with starch concentrations across different parts of the tree. A completely randomized experimental design was employed, and Tukey's comparison of means was utilized for data analysis. In conclusion, our findings confirm a direct relationship between starch levels and both initial and final fruit retention. Aranzazu, in particular, demonstrated higher proportions of flowers with medium and high levels of starch, and it was precisely in this zone where higher initial and harvest values of retained fruit were recorded.